Photosynthetic acclimation responses of maize seedlings grown under artificial laboratory light gradients mimicking natural canopy conditions - Hirth, Matthias; Dietzel, Lars; Steiner, Sebastian; Ludwig, Robert; Weidenbach, Hannah; Pfalz, Jeannette; Pfannschmidt, Thomas (Frontiers in Plant Science, 2013)
In this study we assessed the ability of the C4 plant maize to perform long-term photosynthetic acclimation in an artificial light quality system previously used for analysing short-term and long-term acclimation responses (LTR) in C3 plants. We aimed to test if this light system could be used as a tool for analysing redox-regulated acclimation processes in maize seedlings. Photosynthetic parameters obtained from maize samples harvested in the field were used as control. The results indicated that field grown maize performed a pronounced LTR with significant differences between the top and the bottom levels of the plant stand corresponding to the strong light gradients occurring in it. We compared these data to results obtained from maize seedlings grown under artificial light sources preferentially exciting either photosystem II or photosystem I. In C3 plants, this light system induces redox signals within the photosynthetic electron transport chain which trigger state transitions and differential phosphorylation of light harvesting complexes of photosystem II (LHCII). The LTR to these redox signals induces changes in the accumulation of plastid psaA transcripts, in chlorophyll (Chl) fluorescence values Fs/Fm, in Chl a/b ratios and in transient starch accumulation in C3 plants. Maize seedlings grown in this light system exhibited a pronounced ability to perform both short-term and long-term acclimation at the level of psaA transcripts, Chl fluorescence values Fs/Fm and Chl a/b ratios. Interestingly, maize seedlings did not exhibit redox-controlled variations of starch accumulation probably because of its specific differences in energy metabolism. In summary, the artificial laboratory light system was found to be well-suited to mimic field light conditions and provides a physiological tool for studying the molecular regulation of the LTR of maize in more detail.